LOW-CYCLE FATIGUE OF THE SECOND GENERATION DIRECTIONALLY SOLIDIFIED SUPERALLOY - ZHANG ShiChao; LI Li; HOU XueQin (Jixie qiangdu)
The total strain-controlled low cycle fatigue（ LCF） behaviors of a directionally solidified（ DS） superalloy DZ406 at 950℃ and 1000℃ for R = 0. 05 were investigated. The results of LCF tests indicated that mean stress relaxation occurred under asymmetric straining. The rate of mean stress relaxation increased with the increasing of strain amplitude. All the LCF data obtain under various ratios were well correlated by a modified SWT approach for lifetime prediction,the all data fell into the factor of 3 scatter band. With the increasing of strain amplitude it appeared muti-fatigue crack initiations.